Pelaksanaan Prinsip Corporate Social Responsibility (CSR) Dalam Rangka Menjalankan Kewajiban Perusahaan Taat Hukum Dan Peningkatan Sosial Masyarakat - Salsabila Rohadi; Abim Bhakti; Sumriyah Sumriyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The implementation of CSR can reflect the good or bad image of a company itself, if CSR can be implemented well and in accordance with procedures then this can provide benefits for the company, not only the company, but also for the government, and can improve the welfare of the surrounding community. Company. The concept of CSR itself means that an organization is not only concerned with itself but also pays attention to the rights of the people in its environment. In its implementation, it is necessary to know how a company carries out its responsibilities in implementing CSR in order to improve the welfare of the community, as well as what obstacles the company experiences in implementing CSR. This research uses normative or doctrinal research methods, the data used is primary data obtained from statutory regulations, and secondary data obtained from books, articles related to the research object, as well as tertiary data obtained from the Law Dictionary, Indonesian Dictionary, Encyclopedia, and so on. The data collection uses library research.